Resilient seed systems study tour to Uganda: highlights and insights - Vernooy, Ronnie; Adokorach, Joyce; Subedi, Abishkar (2022)
From 30 May to 3 June 2022, a group of 16 agricultural professionals from government, private sector and non-governmental organizations, coming from Ethiopia, Sudan and South Sudan, travelled to Uganda to learn about the country’s experiences and achievements related to the conservation and sustainable use of plant genetic resources and integrated seed sector development. The tour is part of a larger capacity development initiative “Tailor-Made Training (TMT) Plus Course on Building resilient food systems in protracted crisis situations: Climate change, seed systems and community seed banks,” funded by NUFFIC of the Netherlands, and coordinated by the Wageningen Center for Development Innovation of Wageningen University and Research, and the Alliance of Bioversity International and CIAT. Visits included the Plant Genetic Resources Centre in Entebbe, the Kazo Dryland Husbandry Agro-pastoralists’ Association, the Kalero millet farmers group, the Omutima Gwa Ruhiira Farmers Cooperative Society Limited, the Joy Mugisha and Family Demonstration Farm in Sheema, the Kibuga community seed bank in Kabale, and the bean seed/genebank of the Alliance of Bioversity International and CIAT in Kawanda. This brief presents the highlights and insights gained by the group of 16.